ANALISIS DE LA INFRAESTRUCTURA DE LA RED INFORMATICA Y SOPORTE DEL DISTRITO DE SALUD 12D05 PALENQUE - VINCES - GARCIA GUAMAN, MIGUEL ALFREDO (2019)
The infrastructure of Red Informática, with the passage of years is known as Information Technology (IT), is a branch of Systems Engineering that allows me to discover all the essentials in networks and telecommunications, which is combined by network elements. which are active equipment that its main function is to have the means for transmission and communication in order to support the correct sending of information. In this case study we will analyze the Infrastructure of the Computer Network and Support of the District of Health 12D05 Palenque - Vinces, with this we will know anomalies that exist within the institution with the objective of giving a higher quality and enhancement to the District of Health 12D05 Palenque - Vinces. At present, the Palenque - Vinces 12D05 Health District presents several problems with the network and infrastructure, since it does not have a correct Security policy, there are conflicts with IP addresses, computer equipment failures, Insufficient Bandwidth, Infections of Virus and little preventive maintenance to the infrastructure of Network, There are criteria that when properly fulfilled guarantee a perfect operation of the network, which ensure the security and integrity of the information. The computer support is a service which can be through remote assistance or personal technical service, methods and techniques to solve a problem, also provide advice to users and companies working with computers. (Cruz, 2014).